PENGARUH PENERAPAN SISTEM AKUNTANSI PEMERINTAH DAERAH, PEMAHAMAN AKUNTANSI, DAN KETAATAN PADA PERATURAN PERUNDANGAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DAERAH - Dina Karima; Maslichah Maslichah; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This research was conducted to determine the effect of the application of the local government accounting system, understanding of accounting, and adherence to laws and regulations on the performance accountability of local government agencies. The case study in this research is the sampan regency work unit. The sample used in this study were 78 respondents. This study uses multiple regression analysis. The results of this study are that simultaneously the variables of the Implementation of the Local Government Accounting System (X1), the Accounting Understanding variable (X2) and the Obedience to Laws and Regulations (X3) variables simultaneously have a significant influence on the Performance Accountability of Local Government Agencies. Whereas partially the variable of the application of the local government accounting system has a positive and significant effect on the accountability of the performance of local government agencies. Accounting understanding variables have a positive and significant effect on the performance accountability of local government agencies. The variable of accounting understanding has no effect on the accountability of the performance of local government agencies. Keyword: implementation of local government accounting systems, understanding of accounting, adherence to laws, regulation and performance accountability of local government agencies.